Prevalence and complications of hypothyroidism during pregnancy in western Uttar Pradesh - Chaudhary, Karishma; Mani, Poonam; Yadav, Lalita; Tyagi, Mamta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: This study was designed to know the prevalence of hypothyroidism during pregnancy in western part of Uttar Pradesh and its potential complications. A prospective and comparative clinical study to know prevalence of thyroid disorder in pregnancy and pregnancy outcome was done. Methods: Eight Hundred eighty seven pregnant cases from Department of Obstetrics and Gynaecology, Chattrapati Shivaji Subharti Hospital, Meerut were enrolled in the study from the year 2018 to 2020. Detailed history and physical examination was done. Thyroid Function test (FT3, FT4, TSH and Anti-TPO) were performed after the confirmation of pregnancy. Patients were followed up during entire pregnancy. Thirty seven patients dropped out from the study. Results: In this study, prevalence of thyroid disorder was 27.28% which was high when compared to other regions in India and in other parts of Asia. Subclinical hypothyroidism and Overt hypothyroidism was 16.57% and 10.71% respectively. Subclinical hypothyroidism was more prevalent and hidden, leading to the poor obstetrical outcome and fetal complications. Rate of miscarriage was high in overt hypothyroid patients. Conclusions: Due to the immense impact that the maternal thyroid disorder has on maternal and fetal outcome, prompt identification of thyroid disorders and timely initiation of treatment is essential. Thus, universal screening of pregnant women for thyroid disorder should be considered especially in a country like India where there is a high prevalence of undiagnosed thyroid disorder.